m+4-4m+3=

Simple and best practice solution for m+4-4m+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m+4-4m+3= equation:


m+4-4m+3=0

We simplify the equation to the form, which is simple to understand
m+4-4m+3=0

We move all terms containing m to the left and all other terms to the right.
+1m-4m=0-4-3

We simplify left and right side of the equation.
-3m=-7

We divide both sides of the equation by -3 to get m.
m=2.33333333333

See similar equations:

| (x+2.1)-(0.1x+3)=11 | | x-10403=116 | | 5b=3.55 | | -22+6x=44-5x | | 4x-5=4x+7 | | 4x+5=4x+5 | | 3/2a-14=75 | | (x+2.7)-(0.3x+4)=11 | | -15-v=-24 | | y-2=5/4x | | 6(5-x)-12=2x-3(4+x) | | y=0.25x+21 | | 5n+20=n-24 | | 3p-6=13-4p | | 3(2x+5)=7-(2x) | | n/17=18 | | Dover-8.4=10.2 | | -11n=-154 | | 62.9296x+64.9278y=63.546 | | 1/8(5x-24) | | x^2+7x+35=0 | | 2/7=1/3+a | | 0.25= | | 1023/80=-3/3/10(-3/2+x) | | 3x+3=-3x-12 | | 3p=8p-r | | b+1/6=65 | | 36-7n=1+3(8-6n) | | =(3x-2) | | 62.9296(1.009795073-1.031752943y)+64.9278y=63.54600003 | | 8m-5(m-2)=7 | | -8+5(1+6c)=-27 |

Equations solver categories